Prinsip Non-Interference dan Batas Keterlibatan Politik Multinational Corporation dalam Investasi Asing di Indonesia - Choirunnisa, Salsabillah (Media Hukum Indonesia (MHI), 2025)
Foreign Direct Investment (FDI) plays a crucial role in driving economic growth, yet Multinational Corporations (MNCs) act not only as economic entities but also as political actors capable of influencing public policy within host states. This study examines the Non-Interference Principle and the limits of political involvement by MNCs in the context of foreign investment in Indonesia. Employing a normative juridical and conceptual approach, the research analyzes international and national instruments. The findings reveal that although MNCs are universally prohibited from interfering in the internal political affairs of host states, the absence of explicit, binding provisions regarding political non-interference within Indonesia’s investment law has created significant ambiguity concerning corporate political conduct. This ambiguity opens space for regulatory capture and political lobbying, potentially undermining state sovereignty and public accountability. Strengthening domestic legal norms is therefore essential to ensure the political neutrality of foreign investors and to maintain a stable and equitable investment climate in Indonesia.